Long-Term Care Insurance: Knowledge Barriers, Risk Perception and Adverse Selection - Martin Boyer; Philippe De Donder; Claude Fluet; Marie-Louise Leroux; Pierre-Carl Michaud (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We conduct a stated-choice experiment where respondents are asked to rate various insurance products aimed to protect against financial risks associated with long-term care needs. Using exogenous variation in prices from the survey design, and objective risks computed from a dynamic microsimulation model, these stated-choice probabilities are used to predict market equilibrium for long-term care insurance using the framework developed by Einav et al. (2010). We investigate in turn causes for the low observed take-up of long-term care insurance in Canada despite substantial residual out-of-pocket financial risk. We first find that awareness and knowledge of the product is low in the population: 44% of respondents who do not have long-term care insurance were never o↵ered this type of insurance while overall 31% report no knowledge of the product. We then identify three main causes for the lack of long-term care insurance: asymmetric information, lack of awareness of the insurance products, and misperceptions of risks. We measure the welfare losses associated to these three causes, and obtain much higher welfare losses for lack of awareness (corresponding to 49% of the equilibrium consumer surplus estimated with our data for the baseline contract) than for misperceptions (28%) and especially for adverse selection (1%).
Keywords: 330